ROS in Cancer: The Burning Question. Issue 5 (May 2017) - Chio, Iok In Christine; Tuveson, David A.
Abstract : An unanswered question in human health is whether antioxidation prevents or promotes cancer. Antioxidation has historically been viewed as chemopreventive, but emerging evidence suggests that antioxidants may be supportive of neoplasia. We posit this contention to be rooted in the fact that ROS do not operate as one single biochemical entity, but as diverse secondary messengers in cancer cells. This cautions against therapeutic strategies to increase ROS at a global level. To leverage redox alterations towards the development of effective therapies necessitates the application of biophysical and biochemical approaches to define redox dynamics and to functionally elucidate specific oxidative modifications in cancer versus normal cells. An improved understanding of the sophisticated workings of redox biology is imperative to defeating cancer. Trends: Dietary antioxidants are not prophylactic against cancer, but rather increase the incidence of primary tumor formation and metastasis in experimental animal models. Intravenous administration of high-dose vitamin C worked as a pro-oxidant to suppress tumor formation in murine xenograft models of colon cancer. Nrf2-dependent regulation of redox switches in the protein synthesis machinery promotes human and murine pancreatic tumor maintenance. Many reactive oxygen species (ROS) do not function as nonspecific damaging agents in the cell, but rather as secondary messengers with specific signaling outcomes. Biochemical platforms to identify redox-sensitive cysteine residues are required to decipher the functional consequences of specific redox signaling events in cancer cells. Redox-sensitive probes targeted to different cellular compartments will revolutionize our understanding of in vivo redox signaling in both time and space.